2017
DOI: 10.1515/folmed-2017-0027
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Postpartum Thyroid Dysfunction in Euthyroid Women Prior to Pregnancy

Abstract: Citation: Nonchev BI, Argatska AV, Pehlivanov BK, Orbetzova MM. Risk factors for postpartum thyroid dysfunction in euthyroid women prior to pregnancy. 2017;59(2):190-196. doi: 10.1515/folmed-2017-0027 Background: Thyroid dysfunction is common during the postpartum and the predisposing factors for its development are considered specifi c for the population studied. The aim of this study was to evaluate the risk factors for the occurrence of postpartum thyroid dysfunction (PPTD) in euthyroid women prior to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Advanced age, family history of thyroid diseases, and positive thyroid autoantibody were considered high risk factors for postpartum OH in women with newly diagnosed SCH during pregnancy ( 7 , 9 , 10 ). Recently, one study found that the positive TPOAb in pregnancy and 6 weeks postpartum were high risk factors for persistent hypothyroidism after delivery ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Advanced age, family history of thyroid diseases, and positive thyroid autoantibody were considered high risk factors for postpartum OH in women with newly diagnosed SCH during pregnancy ( 7 , 9 , 10 ). Recently, one study found that the positive TPOAb in pregnancy and 6 weeks postpartum were high risk factors for persistent hypothyroidism after delivery ( 8 ).…”
Section: Discussionmentioning
confidence: 99%